Teke dan Ideologi Wanita dalam Peninggalan Ngada,Nusa Tenggara Timur - Watu Yohanes Vianey (Center for Research and Development of Religious Literature and Heritage, 2023)
The art of teke, which is a part of the Ngadha people's traditional cultural practices, is the material object of this investigation. The formal object concerns the axiology of women's ideology and its existence. What feminist philosophy is expressed in the teke cultural heritage is the central question of this cultural study. This study explores cultural codes based on traditional Ngada hermeneutics in order to analyze the data through qualitative research methods. The research findings offer a fresh perspective on the distinctiveness of the ine weta ideology, which is a set of beliefs about women specific to the matriarchal Ngadha cultural tradition. More than that, ine weta's ideology actually celebrates gender equality through the joy of dance, poetry, and song. This ideology in the art of teke hermeneutics is a variant of the familial ideology, which must be built and purified through teachings, actions, and celebrations in the light of mesu mora (‘charity love’) harmoniously, closely, roundly, and beautifully in the world of life. The conclusion of this writing is that the authors undertake a cultural study in order to contribute to the discussion of women’s equality by proposing one category of woman ideology found in the matriarchal culture of Ngada, namely, the ideology of ine weta (‘mother-sister’) as a variant of familial ideology uncovered in the art of teke.